Shear-dominated interlaminar fracture process in CFRP composite laminates - Koloor, Seyed Saeid Rahimian (2013)
This paper examines and quantifies the mechanics of damage processes leading to interlaminar fracture of composite laminates under shear-dominated loading. For this purpose a 16-ply unidirectional CFRP composite laminate specimen with end-notched flexural (ENF) geometry is tested in a 3-point bend test set-up. The initial crack length to span ratio is a/L = 0.325. The long span of 160 mm induces a gradual evolution of shear-dominated interlaminar damage and fracture. Finite element (FE) simulation of the test is performed with interlaminar cohesive behavior assumed for the midthickness pre-cracked interface. The measured load-deflection of the ENF specimen is used to validate the FE model with cohesive interface. Hypothetical elastic CFRP composite beams with and without interlaminar edge crack are also modelled as reference cases. Results show that the initial crack reduces flexural stiffness by 30.2 pct. with insignificant lamina damage. Interlaminar shear stress and the corresponding shear energy release rate govern the interlaminar fracture process in the cohesive zone. A cohesive zone length of 2.2 mm with maximum relative shear displacement of 0.023 mm is predicted at the onset of interlaminar fracture. The rate of energy dissipation due to interlaminar damage accelerates to 3.75 N.mm/sec in the final.